Digital Resilience Framework for MSME Development in Facing Global Market Volatility - Setyawan, Antonius Ary; Setyawati, Endang; Tyoso, Jaluanto Sunu Punjul (Aptisi Transactions On Technopreneurship (ATT), 2026)
This study aims to develop a Digital Resilience Framework for Indonesian MSME by integrating digital innovation, adaptive capabilities, marketing reach, and strategic collaboration in response to global market volatility. Based on the Dynamic Capabilities Theory, Innovation Diffusion Theory, Resource-Based View, and Network Theory, this study examines how digital innovation is transformed into enhanced SMEs performance through the development of dual capabilities within a collaborative ecosystem. A quantitative approach using SEM-PLS was employed to analyze data from 350 SMEs in Central Java, collected through stratified random sampling. Measurements using a 1-5 Likert scale were used to assess digital innovation, digital adaptive capabilities, digital marketing reach capabilities, SMEs performance, and SMEs collaboration. The findings reveal that digital innovation has a significant influence on digital adaptive capabilities and digital marketing reach, both of which positively impact SMEs performance. However, SMEs collaboration does not significantly moderate the relationship between innovation and capability. These findings emphasize the importance of strengthening adaptive and marketing capabilities as drivers of digital transformation. The study contributes theoretically through an integrative model that demonstrates a sequential transformation process, expands Dynamic Capabilities Theory in a digital context, and challenges conventional assumptions of Network Theory regarding the role of collaboration. Practical implications suggest that SMEs prioritize capability development as a mediating mechanism for digital transformation, while policymakers should design interventions focused on capability development rather than technology adoption alone. This study encourages further research exploring complex forms of collaboration and longitudinal evaluations of SMEs digital capability development.